Comparison of the effects of eight weeks of traditional resistance training and TRX on oxidative and antioxidant indicators in women with type 2 diabetes - Mohsen Akbarpour; Safoora Sabagheyan rad; Narjes Chamani (Shahid Beheshti University, 2023)
Background and Purpose: Type 2 diabetes is one of the most common metabolic diseases known in the world and is the main cause of death in many countries, affecting many people every year. Chronic hyperglycemia caused by type 2 diabetes causes oxidative stress, therefore this study compared the effect of eight weeks of traditional resistance training and Total Body Resistance Exercise (TRX) on some oxidative and anti-oxidative indicators in women with type 2 diabetes.Materials and Methods: Thirty women with type 2 diabetes (age, 40-55 years) participated in the study and randomly were divided into three groups of resistance training (n=10), TRX group (n=10), control group (n=10). The experimental groups performed traditional resistance training and TRX three times a week for eight weeks at an intensity corresponding to 80-65% of a maximum repetition, while the control group did not participate in any training program during this period. Blood samples were taken from all subjects before training and 48 hours after the last training session and were used to determine the serum level of superoxide dismutase (SOD), Glutathione Peroxidase (GPx) and malondialdehyde (MDA). Paired t-test was used to investigate the within-groups differences, and the analysis of covariance using Bonferroni's post-hoc test was used to investigate the differences between groups.Results: Present study showed that after eight weeks of traditional resistance training and TRX, significant increases in SOD and GPX levels were observed in the two experimental groups (p< 0.05). However, no significant difference was observed in the control group. MDA levels decreased in both traditional and TRX resistance training groups. The results of between-group analysis showed that there is no significant difference between the two groups of resistance training and TRX for SOD, GPX and MDA indices (P>0.05).Conclusion: Based on said the findings of present study it could be concluded that both training methods can improve oxidative (SOD and GPX) and anti-oxidative (MDA) indices in women with type 2 diabetes.